Design of nano-modified PVDF matrices for lead-free piezocomposites: Graphene vs carbon nanotube nano-additions. (March 2020) - Krishnaswamy, Jagdish A.; Buroni, Federico C.; García-Macías, Enrique; Melnik, Roderick; Rodriguez-Tembleque, Luis; Saez, Andres
Highlights: Nano-modified PVDF matrices for piezocomposites: Graphene vs CNT nanofillers. Order of magnitude better piezo-response. Reduced matrix hardening compared to CNT-modified designs. Larger window of tolerance on the polycrystallinity of inclusions in graphene-modified design. Abstract: Graphene nano-additions to polymer matrices have demonstrated exceedingly better mechanical properties compared to carbon-nanotube modified matrices. Therefore, in the context of mechanically superior high-performance piezo-composites, graphene-modified composite architectures represent an important design direction. In this paper, we first develop an effective property model for graphene-modified piezoelectric matrices, taking into account the mechanical anisotropy of the matrix. We further evaluate the piezoelectric performance of the matrix architecture which incorporates lead-free BaTiO3 polycrystal inclusions. In order to obtain comparisons with well-established composites, we compare the electro-elastic response of two composite architectures in which the matrix is modified by multiwalled CNTs and graphene respectively. It is seen that, near percolation of the nano-additions, graphene-based systems exhibit an order of improvement in the piezoelectric response compared to the composite without nano modification. This improvement is comparable to CNT-based systems, but the matrix hardening is lesser than half the hardening observed in CNT-modified composites. This feature is due to a considerably smaller percolation threshold of graphene compared to CNTs which brings about percolative conditions at very small filler concentrations. We further investigate the dependence of the electric flux and fields in the graphene-modified piezocomposite on the polycrystallinity of the piezoelectric inclusions to identify the polycrystalline configurations that can lead to improved performance in such nanomodified piezocomposites.